Desacralizing Secularism - Parvez Manzoor (American Journal of Islam and Society, 1995)
No Muslim endeavor to face the intellectual challenge of the western tradition can afford to ignore the critical discourse of postmodernism or fail to recognize the Nietzschean claim about truth's complicity with power. Secularism as truth, as doctrine, therefore, cannot be separated from the theory and practice of secular power. As the praxis of statecraft, secularism claims universal sovereignty, and as the theoriu of history, it subordinates all religious and moral claims to its own version of the truth. The secularist enterprise, furthermore, has been immensely successful in transforming the historical order of our times. But as such, it is a subject proper to the discipline of (political) history and merits the Muslim scholar's fullest attention there. Secularism as a doctrine, as an -ism, on the other hand, falls squarely within the province of philosophy and the history of ideas. In order to apprehend. the secularist gospel and its discontents, one needs to contemplate, as it were, the ideational visage of secularism. It is this aspect of secularism- the mask of truth worn by the secularist will-to-power-that the present article intends to uncover. Thus, the secularism that is examined here is not a sociological theory but rather a philosophical paradigm, not an empirical fact but rather an ideological axiom. This survey is divided further into two parts: secularizing theories in sociology and politics from the focus of the present essay. Secularism in philosophy, theology, and science will be treated in the second installment. Secularism or Sacralization? Secularism, like any darling child, has many names. In contemporary literature it is presented (either humbly) as a rejection of ecclesiastical authority, a model for pluralism, a theory of society, a doctrine of governance or (augustly) as a philosophy of history, a creed of atheism, an epistemology of humanism, or (even more grandiosely) as a metaphysics of immanentism that corresponds to the ultimate scheme of things. Within the academic discourse, it is also customary to accord it an almost Socratic definition and to distinguish its various manifestations as a process of history (seculurizution), a state of mind and culture (secularity), and a theory of truth (secularism). (One may note the close ...